Analysis Of Factors Affecting Entrepreneurial Sustainability - Nunik Kusnilawati; Nurhidayati Nurhidayati; Teguh Ariefiantoro (UIN Raden Mas Said Surakarta, 2020)
The research aims to analyze and test empirically the influence of the variable management of entrepreneurial performance, entrepreneurial orientation, and social competence on the variable of entrepreneurial sustainability, either directly or through competitive advantage variables. The sample is 125 respondents. Data collection was carried out using a questionnaire instrument, using the google form application. Processing data using the Partial Least Square-Structural Equation Modeling method. The results of descriptive analysis show that perceptions of entrepreneurial performance management are 79.68%, entrepreneurial orientation 89.44%, social competence 79.36%, competitive advantage 72.64%, entrepreneurial sustainability 89.28%. The results of quantitative analysis show that performance management, entrepreneurial orientation, and social competence have a positive effect on competitive advantage; Furthermore, performance management has no effect on entrepreneurial sustainability; but entrepreneurial orientation and social competence have a positive effect on entrepreneurial sustainability; then competitive advantage has a positive effect on entrepreneurial sustainability